EQUALITY BEFORE THE LAW: A CRITICAL REVIEW OF LEGAL IMPLEMENTATION IN INDONESIA - Henry Aspan; Agus Adhari; Ansori Maulana (PT. Radja Intercontinental Publishing, 2024)
Criminal Law is part of the national legal system that has been in effect since independence until now. The implementation of criminal law experiences ups and downs along with the development of society and even becomes a sharp focus when it has not provided justice and prosperity and is still considered an instrument of power to protect state administrators and a weapon for ordinary people when fighting criminal law. country. The implementation of criminal law in Indonesia aims to provide protection, peace, order and legal certainty to the community. Although there are objectives that provide protection, especially personal or individual interests in exercising the rights of citizens. Meanwhile, the purpose of this writing is to provide an understanding that Criminal Law is a chain of laws and regulations that apply in Indonesia and its content focuses on the Criminal Code and Criminal Procedure which reaches all levels of society.